Methylene blue intra-arterial staining of resected colorectal cancer specimens improves accuracy of nodal staging: A randomized controlled trial. Issue 11 (November 2016) - Reima, H.; Saar, H.; Innos, K.; Soplepmann, J.
Abstract: Introduction: Metastatic involvement of regional lymph nodes is a major prognostic factor of colorectal cancer, which influences also its treatment strategy. International consensus foresees retrieval of ≥12 lymph nodes from colorectal specimens. The aim of the study was to assess the effect of intra-arterial staining of colorectal specimens with methylene blue on lymph node harvest. Materials and methods: A total of 266 radically operated colorectal cancer patients were randomized into the methylene blue staining and non-staining groups. In the staining group, methylene blue solution was injected into the colorectal specimen's artery after its removal. The specimens were analysed for lymph node count, diameter and metastatic involvement. Results: The median number of lymph nodes was higher in the staining group, 27 (95% CI 23–31%), compared with the control group, 16 (95% CI 14–19, p < 0.001). The number of examined lymph-nodes was ≥12 in 86% of the cases in the staining group and in 69% of the cases in the control group (p = 0.001). In the staining group more small-diameter (≤4 mm) lymph nodes were examined (median number 20.5 vs. 10, p < 0.001). The proportion of patients with metatatic lymph nodes was 42% in the staining group and 43% in the control group (NS). Conclusions: Methylene blue staining improves significantly staging accuracy through finding more small-diameter lymph nodes. It enables to detect ≥12 lymph nodes in the majority of cases. We recommend routine use of this technique in all colorectal resections with curative intent.